TANTANGAN DAN PENERAPAN LITERASI DIGITAL DALAM PENDIDIKAN TRANSFORMATIF MANUSIA DI ERA POST-TRUTH - Dahur, Arnoldus Janssen; Solosumantro, Heribertus (Information Technology Education Department, 2024)
The presence of digital era humans has created a new step in the sustainability of the existential calling of humans that is always running and changing. Social media as an artificial media for digital humans responds to this by providing full contributions through available information and communication facilities. This contrasts with the weak application of digital literacy in human education. The placement of humans in the digital world itself does not immediately apply practical ways of thinking and review to pre-digital era society. Humans are trapped in technical ways of thinking and not critical and constructive. The method used in this study is a qualitative method. Therefore, this study aims to discuss the challenges of digital literacy in the life of the digitalization era and a study of the application of digital literacy in the education of humans in the digital era. The results of the writing show that there are four pillars of digital literacy that are important for introducing and providing an understanding of information and communication technology devices, which include digital skills, digital culture, digital ethics, and digital safety.